Consistency Degrees of Theories in Łukasiewicz Fuzzy and n-Valued Propositional Logic Systems. (20th June 2010) - Zhang, Jiancheng
Abstract : By means of theory of truth degrees of formulas, according to deduction theorems and completeness theorems, the new concepts of consistency degrees and polar index for general theories in Łukasewicz fuzzy andn -valued propositional logic systems are introduced. Moreover, sufficient and necessary conditions for a theoryΓ to be consistent, inconsistent, and fully divergent are obtained. Finally, some important properties of truth degrees of formulas are proposed.